Evaluation of the United Nations Sustainable Development Goal 15.3.1 indicator of land degradation in the European Union. (17th October 2022) - Schillaci, Calogero; Jones, Arwyn; Vieira, Diana; Munafò, Michele; Montanarella, Luca
Abstract: Land degradation is the persistent reduction in the capacity of the land to support human and other life on Earth (IPBES, 2018). This process jeopardizes the provision of ecosystem services. The Sustainable Development Goal (SDG) 15, 'Life on Land', includes efforts to sustainably manage and recover natural ecosystems and restore degraded land and soil. Under the umbrella of SDG 15, the United Nations Convention to Combat Desertification (UNCCD) has defined an indicator framework to monitor progress toward 'land degradation neutrality'. We evaluated the performance of SDG 15.3.1, focusing on "…proportion of land that is degraded over the total land area" for the European Union (EU) using the TRENDS.EARTH software. We assessed the impact of alternative datasets at different spatial resolutions and policy‐relevant data sources for land cover (CORINE) and soil organic carbon (SOC) stock (LUCAS). Our hypothesis was that higher spatial resolution sub‐indicators would better identify the total share of degraded land and provide a clearer picture of the extent of degraded land for the target period. Land productivity trajectories were adjusted using the Water Use Efficiency index that revealed the high share of improving land reported by the NDVI trends. Therefore, it is advisable to use always a climate correction to assess land productivity trends. Replacing default datasets with alternative sub‐indicators allowed the detection of 25–40% more degraded areas. Additionally, the integration with a combined proxy of land degradation (soil erosion >10 Mg ha −1 yr −1, and SOC concentration <1%) identified an additional 50% land degradation and revealed that a large extent of the EU needs restoration measures.